Self-care interventions of community-dwelling older adults: a systematic review and meta-analysis - Estela González-González; Carmen Requena (Frontiers Media S.A., 2023)
IntroductionThe current notion of "care in old age" should be reconceptualized in the ageing societies of the 21st century. Currently, "being old" means that one is actively involved in their care and has the desire to retain control and independence.ObjectiveUnderstand and analyze the efficacy of interventions in the physical and psychological self-care practices of healthy community-dwelling older people.MethodologySystematic review and meta-analysis. The guidelines of the PRISMA guide were followed. The methodological quality of the studies was checked using Cochrane Effective Practice and Organisation of Care criteria, and the search was performed between 2016 and 2021.ResultsOf the 1,866 evaluated, 8 studies met the criteria. The systematic review reveals that self-care interventions focus on physical health-related variables but not on psychological variables. The meta-analysis shows that interventions significantly improve physical health-related variables (care visits, hospital admission, medication, and gait speed).ConclusionSelf-care training programs should include psychological variables to increase health and well-being in healthy older people.